Seismic response of dual concentrically braced steel frames with various bracing configurations. (January 2022) - Seker, Onur
Abstract: Steel dual structures incorporating special concentrically braced frames (SCBFs) and special moment frames (SMFs) are, in general, effective for their high lateral stiffness and ductility. As such, ductile dual CBFs are often treated as a remedy for mitigating permanent drift demands along with the potential drift concentration in isolated stories. However, despite the benefits and interest, the effect of the bracing configuration on the seismic response of the dual concentrically braced systems, designed following the current capacity design approach stipulated in AISC Seismic Provisions, in particular, has not been thoroughly examined to date. The present study aims to shed light on the impact of the bracing scheme on the seismic behavior of dual SCBFs coupled with SMFs as backup frames. For this purpose, 4- and 10-story dual SCBFs with the commonly used chevron, split X, V, and cross X type bracing configurations are designed according to ASCE 7 and AISC 341. Then, the frames are subjected to a suite of ground motions. The nonlinear time-history analysis results are contrasted and discussed in terms of the peak and permanent drift demands, horizontal floor acceleration demands along with brace ductility demands. Graphical abstract: Unlabelled Image Highlights: Bracing configuration effect on the seismic response of the steel dual CBFs has not been thoroughly examined to date. The mean drift demands in the low- and mid-rise dual structures were moderate. Backup frames dissipated less than 10% of the overall inelastic energy dissipation on average. The limits on the acceleration demands specified in the current US building code seem to be reasonable. The median responses in all dual structures were below the recommended permanent drift limits.